REFORMA DO ESTADO: EFEITOS SBRE A RENDA E O EMPREGO NA REGIÃO DO SUBMÉDIO SÃO FRANCISCO (PETROLINA/JUAZEIRO) - Vergolino, Tercina Barbosa Oliveira; Vergolino, José Raimundo Oliveira (Revista Econômica do Nordeste, 1997)
Acervo histórico